2018
DOI: 10.1210/jc.2017-01585
|View full text |Cite
|
Sign up to set email alerts
|

RANKL/RANK Pathway and Its Inhibitor RANK-Fc in Uterine Leiomyoma Growth

Abstract: Treatment with the RANKL/RANK pathway inhibitor RANK-Fc significantly decreased human leiomyoma cell proliferation and tumor growth. This suggests that the RANKL/RANK pathway could serve as a potential target for the prevention and treatment of uterine leiomyoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Our finding that RANKL plays a critical role in regulating LSC function and LM tumorigenesis prompted us to further explore the mechanism underlying dysregulated RANKL gene expression in LM [11]. RANKL is a known P4/PR target gene in mammary glands [20, 21]; therefore, we postulated that the RANKL gene responds to P4/PR signaling differentially between LM and MM tissues, leading to higher RANKL expressions in LM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding that RANKL plays a critical role in regulating LSC function and LM tumorigenesis prompted us to further explore the mechanism underlying dysregulated RANKL gene expression in LM [11]. RANKL is a known P4/PR target gene in mammary glands [20, 21]; therefore, we postulated that the RANKL gene responds to P4/PR signaling differentially between LM and MM tissues, leading to higher RANKL expressions in LM.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported that RANKL is preferentially expressed and specifically upregulated by R5020 in LIC [11], we went on investigating whether the same mechanism (DNA methylation difference in the DMR adjacent to the distal PRBS of RANKL gene) was also involved. We examined the DNA methylation levels and the effects of 5ʹ-aza treatment on RANKL expression in each LM cell population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suggested mechanism for hormone action on leiomyoma stem cells proposes that differentiated stromal cells respond to circulating steroid hormones by secreting paracrine factors, which in turn stimulate stem cell proliferation and tumor expansion (Bulun, 2013). Supporting this model, it was recently shown that a PGR-positive group of cells in uterine leiomyomas secrete receptor activator of nuclear factor kappa-Β ligand (RANKL) following progestin treatment, which induces proliferation of leiomyoma stem cells through its receptor RANK (Ikhena et al, 2018). Endometrial or endometriosis stem cells, which are also deficient in steroid receptors, may also be stimulated via unique paracrine signaling originating from the surrounding steroid receptor-positive cells.…”
Section: Nrs In Endometrial Stem Cellsmentioning
confidence: 99%
“…In the paper published in this issue of Endocrinology by Shimeng Liu and coworkers, the Bulun’s team explore a possible way of reducing leiomyoma lesions through a treatment by an epigenetic modulator, 5’-Aza-Cytidine ( 3 ). Building on their previous results and know-how ( 4 , 5 ), the Bulun’s team was able to separate, from human samples, 3 cell populations by fluorescence assisted cell sorting (FACs) using CD34 and CD49: stem-cell like cells (LSCs), intermediate cells (LICs), and differentiated cells (LDs) that were globally evaluated by transcriptome and methylome analyses. Ribonucleic acid sequencing (RNA-seq) was used for the transcription analysis and MethylCap-Seq for the methylation analysis.…”
mentioning
confidence: 99%